2016
DOI: 10.1371/journal.pntd.0004517
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection and Stillbirths: A Case of Hydrops Fetalis, Hydranencephaly and Fetal Demise

Abstract: BackgroundThe rapid spread of Zika virus in the Americas and current outbreak of microcephaly in Brazil has raised attention to the possible deleterious effects that the virus may have on fetuses.Methodology/Principal FindingsWe report a case of a 20-year-old pregnant woman who was referred to our service after a large Zika virus outbreak in the city of Salvador, Brazil with an ultrasound examination that showed intrauterine growth retardation of the fetus at the 18th gestational week. Ultrasound examinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
283
1
10

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(301 citation statements)
references
References 11 publications
7
283
1
10
Order By: Relevance
“…Hydranencephaly, intracranial calcifications, destructive lesions of the posterior fossa, hydrothorax, ascites, subcutaneous edema, and arthrogryposis have been described in severe cases (68) (69) . It is important to rule out other infectious agents that are known to induce microcephaly (38) (70) before ascribing it to Zika virus infection.…”
Section: Zika Virus and Microcephalymentioning
confidence: 99%
“…Hydranencephaly, intracranial calcifications, destructive lesions of the posterior fossa, hydrothorax, ascites, subcutaneous edema, and arthrogryposis have been described in severe cases (68) (69) . It is important to rule out other infectious agents that are known to induce microcephaly (38) (70) before ascribing it to Zika virus infection.…”
Section: Zika Virus and Microcephalymentioning
confidence: 99%
“…A recent laboratory study showed that ZIKV affects human brain cells, reducing their viability and growth 31 . ZIKV disease has also been associated with other neurological complications, including GBS 15,32 , meningoencephalitis 33 , microcephaly with agyria and hydrocephalus 7 , hydranencephaly, intracranial calcifications 5,7 , and ocular findings such as bilateral macular and perimacular lesions, and optic nerve abnormalities 34 .…”
Section: A Review Of Icd Codes In the Con-text Of Zikv Outbreaks And mentioning
confidence: 99%
“…Recent studies have shown that ZIKV infection damages the central nervous system, causing fetal malformations 1 and certain neuropathies such as GuillainBarré Syndrome [2][3][4][5] . The virus's neurotropic behavior and its ability to cross the placental barrier and cause brain damage during fetal development have been demonstrated in laboratory experiments 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…int/mediacentre/news/statements/2016/1st-emergency-com mittee-zika/en/). The ZV has also raised attention to the possible deleterious effects that it may have on foetuses [12]. However, ''there are no licensed medical counter measures (vaccines, therapies or preventive drugs) available for Zika virus infection and disease'' [8].…”
mentioning
confidence: 99%